2015
DOI: 10.1007/s00436-015-4762-y
|View full text |Cite
|
Sign up to set email alerts
|

Trichinella spiralis infection changes immune response in mice performed abdominal heterotopic cardiac transplantation and prolongs cardiac allograft survival time

Abstract: Allograft rejection has been an obstacle for long-term survival of patients for many years. Current strategies for transplant rejection are not as optimal as we expected, especially for long-term treatments. Trichinella spiralis, a nematode parasitized in mammalian muscle and as an invader, maintains harmonious with host in the long term by evading host immune attack. To determine whether T. spiralis infection impacts on allograft rejection, we performed mice cardiac allograft transplantation model by using BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…In addition to inducing anti-inflammatory immune response, Trichinella and its ESP also have the ability to reduce immune rejection. Mice that were infected with T. spiralis showed higher survival rates after solid organ transplantations, suggesting that the ESP released by T. spiralis may provide an anti-allograft rejection immune response ( Deng et al, 2016 ).…”
Section: Immune-related Diseases and Cancermentioning
confidence: 99%
“…In addition to inducing anti-inflammatory immune response, Trichinella and its ESP also have the ability to reduce immune rejection. Mice that were infected with T. spiralis showed higher survival rates after solid organ transplantations, suggesting that the ESP released by T. spiralis may provide an anti-allograft rejection immune response ( Deng et al, 2016 ).…”
Section: Immune-related Diseases and Cancermentioning
confidence: 99%
“…The smallest improvement to allograft survival was seen with skin allografts. This effect was well-modeled within one investigation of the effects of 300 T. spiralis larvae on both heart and skin allografts (37). Whilst the allograft survival of both transplant types was prolonged with helminth administration when compared to control, the effect in the heart model was greater, with graft survival extended to 23.4 days in comparison to 10.6 days for control (p < 0.01).…”
Section: Allograft Typementioning
confidence: 82%
“…One study investigated both skin and heart allograft models (37). Helminth intervention varied according to species/genus, parasite burden, live or product based and administration route.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The results of this study showed no significant difference in the production of IFN-γ, IL-9, TGF-β and IL-4 cytokines at different days of the first week after challenge. Th1 immune response is characterized by the production of pro inflammatory cytokine such as interferon gamma [17], while Th2 is characterized by the production of interleukin-4 (IL-4) cytokine [49]. TGF-β is an important pleiotropic cytokine with potent immunoregulatory properties and is essential for the maintenance of immunological self-tolerance.…”
Section: Discussionmentioning
confidence: 99%